Impact of dietary supplementation of β-hydroxybutyric acid on performance, nutrient digestibility, organ development and serum stress indicators in early-weaned goat kids - Mahmoud M. Abdelsattar; Einar Vargas-Bello-Pérez; Yimin Zhuang; Yuze Fu; Naifeng Zhang (Animal Nutrition, 2022)
The objective of this study was to determine the effect of dietary supplementation of β-hydroxybutyric acid (BHBA) on performance, nutrient digestibility, organ development, and serum composition in early-weaned goat kids. Sixty-four goat kids at 30 d of age were assigned to 4 treatments in a completely randomized design: 1) control (basal diet); 2) low (basal diet with 3 g/d per animal BHBA); 3) medium (basal diet with 6 g/d per animal BHBA; and 4) high (basal diet with 9 g/d per animal BHBA). Subsequently, 48 (6 kids per treatment) goat kids were randomly selected and slaughtered at 60 and 90 d of age. Compared with the control group, BHBA at low and high doses increased body weight (P < 0.05), average daily gain (P < 0.01), and average daily starter intake (P < 0.01). The BHBA improved organ development, especially at the lowest dose (P < 0.01). The digestibility of dry matter and crude protein increased with age (P < 0.05). However, BHBA did not affect nutrient digestibility. Compared with the control group, serum ceruloplasmin increased (P < 0.05) with high BHBA level at 90 d of age. However, the serum creatinine (P < 0.05) increased over time but was not affected by BHBA. The serum total antioxidant capacity and superoxide dismutase decreased with the high dose of BHBA at 90 d of age (P < 0.01). In contrast, the serum glutathione peroxidase and malondialdehyde increased with the high doses of BHBA (P < 0.01). Overall, low doses of BHBA were positive for growth performance, organ development, and health status against weaning stress. Whereas high doses of BHBA in the long term could negatively affect antioxidant status.